Database tools for risk analysis of fungal plant pathogen incursions into New Zealand - Everett, K.R.; Pushparajah, I.P.S.; Viljanen-Rollinson, S.L.H.; Marroni, M.V. (New Zealand Plant Protection, 2008)
A prototype database has been developed to provide an uptodate New Zealandspecific resource for use by risk assessors An updated list of biosecurity risk plant fungal pathogens has been compiled for apples grapes kiwifruit barley wheat and potato crops Based on analysis of the literature the most important factors for risk assessments for fungal plant pathogen incursions are for rusts proximity to New Zealand of the disease source and for other fungi the presence in the source country of biosecurity risk pathogens Pathway analysis (including wind pattern modelling for rust incursions) is also an important component of risk assessment For both groups of fungi to determine the risk of establishment and invasiveness the climatic parameters (temperature and humidity) for spore germination and infection are required The economic impact of specific incursions has also been estimated All these factors have been included in the database and the risks of incursions have been calculated on this basis